The Cauchy Problem for Some Dispersive Wave Equations (Journal of Partial Differential Equations, 2020)
"In this paper, we consider the Cauchy problem for some dispersive equations. By means of nonlinear estimate in Besov spaces and fixed point theory, we prove the global well-posedness of the above problem. What's more, we improve the scattering result obtained in [1]."